Significance of intermodal freight modal choice criteria: MCDM-based decision support models and SP-based modal shift policies - Gohari, Adel; Ahmad, Anuar; Balasbaneh, Ali Tighnavard; Gohari, Ali; Hasan, Razi; Sholagberu, Abdulkadir Taofeeq (Elsevier, 2022)
This paper reviews modal choice decisions associated with intermodal freight transportation through decision support models based on the Multi-Criteria Decision-making (MCDM) techniques and modal shift policy assessments based on the Stated Preferences (SP) experiments. The objectives were to determine the relevant decision criteria and their relative significance, to define methods in use, and to identify respective policies that boost intermodality. Google Scholar database and manual search using identified keywords were conducted and references of the relevant articles were double-checked. Consequently, a total of 27 articles consisting of respective 18 and 9 MCDM-based and SP-based articles were reviewed in this study. The results showed that the most commonly used decision criteria were cost, CO2 emissions, delivery time, safety, reliability, flexibility, and frequency. The cost factor was assigned the highest weight in 22 articles (or 81.4%). Analytical Hierarchy Process (AHP) technique was implemented in 12 out of 18 MCDM articles (or 66.6%)). Successful application of MCDM methods (both single and integrated) showed the suitability of these methods for intermodal freight modal choice decision-making. The results of SP experiments revealed that cost reduction policies are more effective than policies addressing other factors to increase the demand for intermodal transportation.